The Role of Training Needs Assessment and Off-the-Job Training Methods on the Performance of Employees at the Investment and One-Stop Integrated Services Office of Gorontalo Province - Suronoto, Mohammad Dimas; Mendo, Andi Yusniar; Biki, Syamsul B. (Jurnal Manajemen Bisnis, 2026)
Optimal employee performance is crucial for the effectiveness of public service organizations; however, empirical evidence regarding specific influencing factors such as training needs assessment and off-the-job training methods remains limited in the Indonesian context. This quantitative study addresses this gap by examining the impact of both variables on the performance of 46 Civil Servants, using questionnaires and multiple linear regression analysis. The results show that both training needs assessment (t-value=3.458) and off-the-job training (t-value=2.024) have a significant positive effect on performance, both partially and simultaneously (F-value=11.958), with the regression model Y = 21.212 + 0.313X₁ + 0.155X₂ explaining 26.6% of the variance in performance. These findings contribute practical empirical evidence that strategic investment in both training aspects can be an effective measure to enhance human resource performance in public organizations, while also highlighting the need to explore other factors for more comprehensive interventions.